The Inluence Of Concentrator Size, Reflective Material And Solar Irradiance On The Parabolic Dish Heat Transfer - Ab Ghani, Mohd Ruddin; Affandi, Rosnani; Gan, Chin Kim; Raman, Siti Hajar; Jano, Zanariah (Indian Society Of Education And Environment & Informatics Publishing Limited, 2014)
-